Teacher Problems in Class III Thematic Learning During the Covid-19 Pandemic in Elementary Schools: Problematika Guru Dalam Pembelajaran Tematik Kelas III Pada Masa Pandemi Covid-19 di Sekolah Dasar - Akhmad Dhani Al Azami; Supriyadi Supriyadi (Universitas Muhammadiyah Sidoarjo, 2021)
This research is a qualitative research. This study discusses the problems of teachers in class III thematic learning during the Covid-19 pandemic at Bluru Kidul 2 Sidoarjo State Elementary School. The purpose of this study is to describe the process of implementing thematic learning for grade III students during the pandemic, the problems faced by teachers in the distance learning process in thematic learning for grade III students, and the data collection techniques used were observation, interviews and documentation. The results of the research are Efforts to overcome the problems of teachers in implementing thematic learning during the covid-19 pandemic, namely parents must provide time availability to accompany children during learning, teachers can come to students' homes from time to time to provide teaching materials to students or contact parents directly. students to give assignments, the teacher does not have to give many assignments to students so that they do not feel burdened remembering that assignments do not only come from one subject.